Kinetic analyses and pyrolytic behavior of Para grass (Urochloa mutica) for its bioenergy potential - Ahmad, Muhammad Sajjad; Mehmood, Muhammad Aamer; Al Ayed, Omar S.; Ye, Guangbin; Luo, Huibo; Ibrahim, Muhammad; Rashid, Umer; Arbi Nehdi, Imededdine; Qadir, Ghulam (Bioresource technology, 2017)
•Para grass is a source of low-cost and abundant biomass.•TGA-DSC analyses were performed to understand kinetics of pyrolysis.•Thermodynamics parameters indicate the bioenergy potential of this novel biomass.•The bioenergy potential of the biomass is comparable with established bioenergy crops. The biomass of Urochloa mutica was subjected to thermal degradation analyses to understand its pyrolytic behavior for bioenergy production. Thermal degradation experiments were performed at three different heating rates, 10, 30 and 50°Cmin−1 using simultaneous thermogravimetric-differential scanning calorimetric analyzer, under an inert environment. The kinetic analyses were performed using isoconversional models of Kissenger-Akahira-Sunose (KAS) and Flynn–Wall–Ozawa (FWO). The high heating value was calculated as 15.04MJmol−1. The activation energy (E) values were shown to be ranging from 103 through 233 kJmol−1. Pre-exponential factors (A) indicated the reaction to follow first order kinetics. Gibbs free energy (ΔG) was measured to be ranging from 169 to 173kJmol−1 and 168 to 172kJmol−1, calculated by KAS and FWO methods, respectively. We have shown that Para grass biomass has considerable bioenergy potential comparable to established bioenergy crops such as switchgrass and miscanthus.